No evidence for BRAF-V600E mutations in gastroeosophageal tumors: results from a high-throughput analysis of 534 cases using a mutation-specific antibody - Preusser, Matthias; Bergmeister-Berghoff, Anna Sophie; Capper, David; Deimling, Andreas von; Maroske, Florian; Brodowicz, Thomas; Hejna, Michael; Birner, Peter; Schoppmann, Sebastian F. (Applied immunohistochemistry & molecular morphology, 2013)
Background: BRAF-V600E mutations are found in a broad spectrum of cancer types and can be successfully targeted by specific therapeutic compounds. Little data on the prevalence of BRAF-V600E mutations in tumors of the upper gastrointestinal tract are available. Materials and Methods: We constructed tissue microarrays of formalin-fixed and paraffin-embedded specimens of 534 gastroesophageal tumors (119 squamous cell cancers and 72 adenocarcinomas of the esophagus, 63 cancers of the gastroesophageal junction/cardia, 199 gastric cancers of the corpus or antrum, 81 gastric gastrointestinal stromal tumors) and performed anti-BRAF-V600E immunostaining using the mutation-specific antibody VE1. As control tissue we used 3 melanoma cases with confirmed BRAF-V600E mutation and distinct VE1 immunostaining. Results: None of the gastroesophageal tumor cases showed a positive immunostaining signal. Conclusions: BRAF-V600E mutation is not a relevant oncogenic driver in gastroesophageal tumors. Immunohistochemical analysis using mutation-specific antibodies on tissue microarrays is a feasible, time-efficient and cost-efficient approach to high-throughput screening for specific mutations in large tumor series.